Analysis Of Factors Causing Sexual Deviance (Lesbian) In Adolescents In The Coastal Region Of Southeast Sulawesi: Sexual Deviance (Lesbian) - Pati, Wisnu Catur Bayu; Asri, Andi; Siradjuddin, M. Syukri (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Adolescence is a transitional phase that causes a lot of turmoil both positive and negative. One of the developmental tasks of adolescence is being able to accept and understand their sexual role. Teenagers begin to understand and have sexual attraction to the opposite sex. However, the fact is that there are many deviations in adolescence, one of which is the tendency to like the same sex and not be sexually attracted to the opposite sex. Of course, there are many factors behind this condition. This study aims to analyze the various factors that cause the emergence of sexual deviation (lesbi) in female adolescents. Methods: This study uses a qualitative method with a phenomenological approach. The participants involved in this study were 3 female adolescents with sexual deviation (Lesbian). The data collection techniques used were observation and in-depth interviews. Data analysis used descriptive qualitative and then continued with data triangulation. Results: This research resulted in 4 main factors for the emergence of sexual deviant behavior (Lesbi) including: 1) Environmental factors 2) Psychological factors (trauma); 3) Family factors; 4). Curiosity; Conclusions: sexual deviant behavior (lesbi) appears with a variety of factors and backgrounds. So it is very necessary for special handling and prevention so that this behavior does not spread widely and become a destroyer of future generations.